Study of MASnI3 perovskite photodetectors prepared by the inverse temperature crystallization method in ambient atmosphere and the spin coating method in a glovebox - Weng, Wei-Sung; Chien, Yu-Ching; Lee, Tsung-Yen; Chen, Lung-Chien (Frontiers in Materials, 2025)
In this study, we prepared MASnI3 lead (Pb)-free halide perovskite metal-semiconductor-metal-type photodetectors through the inversion crystallization method under an atmospheric environment and the spin-coating method in a glove box, respectively. The scanning electron microscopy (SEM) images revealed the different surface morphology. They show two types of growth models: the inverse temperature crystallization (ITC) method uses solvent volatilization, and the spin-coating method is a reaction between precursors. For the MASnI3 perovskite film obtained through the inversion crystallization method, a broad band of photoluminescence (PL) spectrum at approximately 470 nm, corresponding to the level transition of 2.638 eV, was observed. On the other hand, for the MASnI3 perovskite film obtained through the spin-coating method, a narrow band of the photoluminescence spectrum at approximately 773 nm, corresponding to the level transition of 1.604 eV, was observed. This is the Burstein–Moss shift environment due to the introduction of oxygen. In addition, the photocurrent of a device prepared in a glove box is two orders of magnitude higher than that of the device prepared by the ITC method.